Mechanism of implicit moral decision in the context of non-deceptive counterfeit luxury consumption - Jin, Jia; Dai, Lu; Li, Taihao; Xu, Ting; Ma, Baojun; Pei, Guanxiong (Current psychology (New Brunswick, N.J.), 2024)
The implicit moral decision exists widely in our daily life, such as the non-deceptive counterfeit luxury consumption, but its moral decision mechanism remains to be clarified. This study is dedicated to studying how moral beliefs affect individuals’ moral decision process and decision outcomes in implicit moral decisions, as well as the effect of attitude function, which can impact the implicit degree of moral decision. We employed transcranial direct current stimulation (tDCS) to examine neural underlying and effect of moral belief on counterfeit luxury consumption. In this study, we adopted 2 (stimulation group: active vs. sham, between-subject) × 2 (attitude function: social-adjustive vs. value-expressive, within-subject) mixed design. 58 participants were randomly assigned to either active or sham tDCS groups (a-tDCS vs. s-tDCS). Our results showed that the moral belief of counterfeit luxury consumption was higher for a-tDCS group (left anodal/right cathodal tDCS over dorsolateral prefrontal cortex) than s-tDCS group (sham stimulation). The counterfeit luxury purchase intention of s-tDCS group is higher. Moreover, we also found reaction time of value-expressive function is longer for a-tDCS group. Hence, these results suggested that moral beliefs can change implicit moral decisions, which is also related to left dorsolateral prefrontal cortex (DLPFC). Besides, attitude functions can affect the relationship between moral beliefs and moral decision processes. In summary, the current study’s research findings can help understand and solve the social problems caused by implicit moral decisions.